2015
DOI: 10.1002/2014tc003766
|View full text |Cite
|
Sign up to set email alerts
|

Eocene and Miocene extension, meteoric fluid infiltration, and core complex formation in the Great Basin (Raft River Mountains, Utah)

Abstract: Metamorphic core complexes (MCCs) in the North American Cordillera reflect the effects of lithospheric extension and contribute to crustal adjustments both during and after a protracted subduction history along the Pacific plate margin. While the Miocene‐to‐recent history of most MCCs in the Great Basin, including the Raft River‐Albion‐Grouse Creek MCC, is well documented, early Cenozoic tectonic fabrics are commonly severely overprinted. We present stable isotope, geochronological (40Ar/39Ar), and microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 73 publications
(259 reference statements)
3
23
0
Order By: Relevance
“…This places the Pioneer metamorphic core complex in an important geographic and temporal position at the junction of the northern and central belts of metamorphic core complexes. The central belt of metamorphic core complexes includes the Raft River-Albion-Grouse Creek metamorphic core complex (Utah), located just south of the Snake River Plain, and the Ruby Mountain-East Humboldt and Snake Range metamorphic core complexes farther south in Nevada; these metamorphic core complexes display Eocene to Miocene extension (e.g., McGrew and Snee, 1994;MacCready et al, 1997;Miller et al, 1999;Sullivan and Snoke, 2007;Wells et al, 2000;Colgan et al, 2010;Gans et al, 2011;Konstantinou et al, 2012Konstantinou et al, , 2013Methner et al, 2015). The southern belt of metamorphic core complexes, from Arizona to Mexico, records significant Miocene extension, lower magnitudes of exhumation, and small amounts of partially molten crust (e.g., Foster et al, 1993;Scott et al, 1998).…”
Section: Regional Geologymentioning
confidence: 99%
“…This places the Pioneer metamorphic core complex in an important geographic and temporal position at the junction of the northern and central belts of metamorphic core complexes. The central belt of metamorphic core complexes includes the Raft River-Albion-Grouse Creek metamorphic core complex (Utah), located just south of the Snake River Plain, and the Ruby Mountain-East Humboldt and Snake Range metamorphic core complexes farther south in Nevada; these metamorphic core complexes display Eocene to Miocene extension (e.g., McGrew and Snee, 1994;MacCready et al, 1997;Miller et al, 1999;Sullivan and Snoke, 2007;Wells et al, 2000;Colgan et al, 2010;Gans et al, 2011;Konstantinou et al, 2012Konstantinou et al, , 2013Methner et al, 2015). The southern belt of metamorphic core complexes, from Arizona to Mexico, records significant Miocene extension, lower magnitudes of exhumation, and small amounts of partially molten crust (e.g., Foster et al, 1993;Scott et al, 1998).…”
Section: Regional Geologymentioning
confidence: 99%
“…Infiltration of meteoric fluids has been documented in the footwall of detachment zones that bound the metamorphic core complexes of the North American Cordillera, based mainly on the low hydrogen (δD) and oxygen (δ 18 O) isotope values of synkinematic hydrous minerals [e.g., Fricke et al ., ; Losh , ; Mulch et al ., , ; Holk and Taylor , ; Gottardi et al ., ; Gébelin et al ., , , ; Methner et al ., ; Quilichini et al ., , ], the Menderes Massif of Turkey [ Hetzel et al ., ], and extensional detachments in the European Central Alps [ Campani et al ., ]. Surface fluids penetrated the deforming crust down to the brittle‐ductile transition in these orogens by means of normal faults and fractures that dissected the brittle upper crust, while at the same time movement within the detachment zone induced advection of hot footwall material that promoted buoyancy‐driven fluid convection [e.g., Person et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of fluids during deformation in midcrustal shear zones associated with MCCs has long been recognized (Fricke et al, 1992;Gébelin et al, 2011Gébelin et al, , 2014Gottardi et al, 2011Gottardi et al, , 2015Kerrich & Rehrig, 1987;Methner et al, 2015;Mulch et al, 2004Mulch et al, , 2007Quilichini et al, 2015Quilichini et al, , 2016Wickham et al, 1993). Some isotopic studies have identified the source of synkinematic fluids as basinal brines (Roddy et al, 1988;Spencer & Welty, 1986), magmatic or metamorphic in origin (Axen, 1992;Kerrich & Rehrig, 1987;Smith et al, 1991Smith et al, , 2008, or mixing of multiple sources (Nesbitt & Muehlenbachs, 1995;Spencer & Welty, 1986).…”
mentioning
confidence: 99%
“…Some isotopic studies have identified the source of synkinematic fluids as basinal brines (Roddy et al, 1988;Spencer & Welty, 1986), magmatic or metamorphic in origin (Axen, 1992;Kerrich & Rehrig, 1987;Smith et al, 1991Smith et al, , 2008, or mixing of multiple sources (Nesbitt & Muehlenbachs, 1995;Spencer & Welty, 1986). Other isotopic and field-based studies suggest circulation of surface-derived fluids that penetrate to 10-15-km depths (Fricke et al, 1992;Gébelin et al, 2011Gébelin et al, , 2014Gottardi et al, 2011Gottardi et al, , 2015Kerrich & Rehrig, 1987;Methner et al, 2015;Mulch et al, 2004Mulch et al, , 2007Quilichini et al, 2015Quilichini et al, , 2016Wickham et al, 1993). The mechanism by which surface-derived water is pumped beyond the brittle-ductile transition is conceptually challenged by physiomechanical process (e.g., Connolly & Podladchikov, 2004;Fusseis et al, 2009;Lyubetskaya & Ague, 2009;Menegon et al, 2015;Yardley, 2009).…”
mentioning
confidence: 99%